“Rigid” structure is a key determinant for the low digestibility of myoglobin - Li, Qian (Food Chem X, 2020)
Myoglobin, a critical protein responsible for meat color, has been shown insusceptible to digestion. The underlying mechanism is not clear. The present study aimed to evaluate whether the structural properties of myoglobin are associated with its insusceptibility to digestion using spectroscopic and computational techniques. Myoglobin was degraded by only 7.03% by pepsin and 33.00% by pancreatin. The structure of myoglobin still maintained α-helix after the two-step digestion, with the exposure of some aromatic residues. In addition, molecular dynamics modeling suggested that hydrophobic amino acid residues (Phe 111, Leu 10, Ala 115, Pro 116) in pepsin and polar amino acid residues (Tyr 146, Thr 95) in myoglobin were found in the proximity of binding sites, which could result in the low digestibility of myoglobin. Our findings provide a new insight into the underlying mechanisms on the difficulty in digestion of myoglobin.